The impact of digital learning on numeracy: A meta-analysis from the perspective of Indonesian education policy implementation - Samsul Maarif; Rully Charitas Indra Prahmana; Krisna Satrio Perbowo (KALAMATIKA Jurnal Pendidikan Matematika, 2026)
Although various studies have discussed digital learning in mathematics education, to date there has been no comprehensive meta-analysis that systematically measures the impact of digital interventions on Indonesian students’ numeracy skills and their relationship to national education policies. This study presents a meta-analysis of 25 empirical studies involving 1,387 participants, aimed at measuring the effectiveness of digital learning in improving Indonesian students’ numeracy skills from 2015 to 2025The analysis shows an average effect size of 1.218, which is considered high, indicating that the integration of digital media has a significant impact on students’ conceptual understanding and numerical reasoning. The most effective digital interventions identified were the Wordwall application, educational TikTok content, and augmented reality flipbooks, which combine interactivity, visualization, and active student engagement. Overall, the meta-analysis confirms that digital media integration effectively improves students’ numeracy skills and aligns with the implementation of the Independent Curriculum and the Digital Education Transformation policy. However, the relevance of these findings should be reconsidered in light of ongoing policy changes and technological developments. Further research is needed to examine moderating variables such as gender, socioeconomic background, and the digital literacy of both teachers and students.